Determinants of Demand for Life Insurance: The Case of Canada - Mapharing, Mogotsinyana; Otuteye, Eben; Radikoko, Ishmael (Journal of Comparative International Management, 2016)
This study examines the determinants of demand for life insurance in Canada. Lewis (1989) model is used to identify the determinants of life insurance demand. However, based on the findings by Stock and Watson (1988) of possible spurious regression, especially in light of our limited dataset, we focussed on testing for co-integration to establish long-run equilibrium among identified variables rather than estimating a demand model. The Johansen co-integration methodology was applied. The results confirm that education, income, inflation, social security, interest rates, dependency ratio, financial development and life expectancy have long term equilibrium relationship with life insurance. An interesting result was that co-integration between income and demand for life insurance occurred after a 3-year lag period. On the basis of the permanent income hypothesis, an interpretation of this result could be that people wait to make sure that their increase in income is permanent before they increase their spending on certain items, including life insurance. While this study does not produce a definitive structural demand model for life insurance, the results provide a valid basis for governments and other life insurance policy makers across the globe to focus on certain key variables as potential drivers of demand for life insurance.